Psychometric properties of the emotional quotient inventory-short form (EQI-SF) in Mexicans - Ruvalcaba-Romero, Norma A. (2020)
Emotional intelligence is considered a protective factor against a variety of psychosocial problems. Due the relevance of this construct, a variety of instruments have been designed for its evaluation, among which the EQi-SF stands out; The objective of this work was to identify the psychometric properties of the EQi-SF in the Mexican population. The study was carried out in a sample of 829 high school graduates in the state of Jalisco, Mexico. The 28-item version of the EQi-SF was applied with a 5-point Likert structure that evaluates 4 factors: Intrapersonal Competence, Interpersonal Competence, Stress Management and Adaptability. Factorial analyzes were carried out, from which a four-dimensional factorial structure with adequate fit indices was corroborated, as well as acceptable to good reliability levels. The results are contrasted in the light of previous studies and implications and recommendations are discussed.